Linguistic Profile Test (LPT) in Nepali Language - Karna, Sureshwar Lal; Karantha, Pratibha; Khanal, Kabiraj (Nepalese Journal of ENT Head and Neck Surgery, 2014)
DOI: http://dx.doi.org/10.3126/njenthns.v3i2.10153 Nepalese Journal of Head and Neck Surgery Vol.3(2) 2012: 8-9     =    5         1     =5     *"        057.7                        "(            #                        .    !#        ##    /&        #    H)&&2)&&+    G    J     "(                #     7$            ##                 .F0    !$             )B?%&)A2&&#)BBAB7$*B)     9            0    ! =5                      #